A methodology to determine the elastic moduli of crystals by matching experimental and simulated lattice strain pole figures using discrete harmonics. (March 2017) - Wielewski, Euan; Boyce, Donald E.; Park, Jun-Sang; Miller, Matthew P.; Dawson, Paul R.
Abstract: Determining reliable single crystal material parameters for complex polycrystalline materials is a significant challenge for the materials community. In this work, a novel methodology for determining those parameters is outlined and successfully applied to the titanium alloy, Ti-6Al-4V. Utilizing the results from a lattice strain pole figure experiment conducted at the Cornell High Energy Synchrotron Source, an iterative approach is used to optimize the single crystal elastic moduli by comparing experimental and simulated lattice strain pole figures at discrete load steps during a uniaxial tensile test. Due to the large number of unique measurements taken during the experiments, comparisons were made by using the discrete spherical harmonic modes of both the experimental and simulated lattice strain pole figures, allowing the complete pole figures to be used to determine the single crystal elastic moduli. Graphical abstract: Image 1